Объяснение:
Рівняння : z• | z | - 2z + 1 = 0 ;
1 ) | z | ≥ 0 ; тоді z • z - 2z + 1 = 0 ; 2) | z | < 0 , тоді - z•z - 2z + 1 = 0 ;
z² - 2z + 1 = 0 ; z² + 2z - 1 = 0 ;
D = 4 - 4 = 0 ; z = 2/2 = 1 ; D = 4 + 4 = 8 > 0 ;
| z |= 1 ≥ 0 ; z₁ = (- 2 -2√2 )/2 = - 1 - √2 ; z₂= - 1 + √2 /
для z₂ | z | < 0 - невірно .
В - дь : z = 1 ; z = - 1 - √2 - корені рівняння .
=y(y-2)^2 - 3(y-2) = (y-2)(y^2 - 2y - 3).
B) (y^2 +1)*b^2 - b^4 - y^2 = b^2*y^2 + b^2 - b^4 - y^2 =
= (b^2*y^2 - y^2) -(b^4 - b^2) = y^2(b^2 - 1) - b^2(b^2 -1) =
=(b^2 - 1)*(y^2 -b^2)=(b-1)(b+1)(y-b)(y+b).